Towards implementation of a benthic microbial fuel cell in lake Furnas (Azores) : phylogenetic affiliation and electrochemical activity of sediment bacteria - Martins, Gilberto (2010)
This work was conducted to examine the composition and electrochemical activity of the bacterial community inhabiting lake Furnas sediments (Azores). Fingerprinting analysis of the bacterial 16S rRNA gene fragment was done by denaturing gradient gel electrophoresis. The sequences retrieved from lake Furnas sediments were affiliated to Bacteroidetes/Chlorobi group, Chloroflexi, Alfa-, Delta-, and Gamma-subclasses of Proteobacteria, Cyanobacteria, and Gemmatimonadetes. A cyclic voltammetric study was carried out with an enriched sediment bacterial suspension in a standard two chamber electrochemical cell using a carbon paper anode. Cyclic voltammograms (scan rate of 50 mV/s) showed the occurrence of oxidation–reduction reactions at the carbon anode surface. The benthic microbial fuel cell operated with lake Furnas sediments presented a low power density (1 mW/m2) indicating that further work is required to optimise its power generation. These results suggested that sediment bacteria, probably from the Delta- and Gamma-subclasses of Proteobacteria, were electroactive under tested conditions.